SCGICAR: Spatial concatenation based group ICA with reference for fMRI data analysis. (September 2017) - Shi, Yuhu; Zeng, Weiming; Wang, Nizhuan
Highlights: A novel SCGICAR method was proposed based on multi-objective optimization. PCA was used to extract the temporal priori information from group subjects. The post-processing means were adopted to obtain group spatial component and individual temporal component. The functional connectivity detection ability of SCGICAR has been improved on both single-subject and group-subjects levels. Abstract: Background and Objective: With the rapid development of big data, the functional magnetic resonance imaging (fMRI) data analysis of multi-subject is becoming more and more important. As a kind of blind source separation technique, group independent component analysis (GICA) has been widely applied for the multi-subject fMRI data analysis. However, spatial concatenated GICA is rarely used compared with temporal concatenated GICA due to its disadvantages. Methods: In this paper, in order to overcome these issues and to consider that the ability of GICA for fMRI data analysis can be improved by adding a priori information, we propose a novel spatial concatenation based GICA with reference (SCGICAR) method to take advantage of the priori information extracted from the group subjects, and then the multi-objective optimization strategy is used to implement this method. Finally, the post-processing means of principal component analysis and anti-reconstruction are used to obtain group spatial component and individual temporal component in the group, respectively. Results: The experimental results show that the proposed SCGICAR method has a better performance on both single-subject and multi-subject fMRI data analysis compared with classical methods. It not only can detect more accurate spatial and temporal component for each subject of the group, but also can obtain a better group component on both temporal and spatial domains. Conclusions: These results demonstrate that the proposed SCGICAR method has its own advantages in comparison with classical methods, and it can better reflect the commonness of subjects in the group.